Incidence of AIDS and excess of mortality associated with HIV in haemophiliacs in the United Kingdom: report on behalf of the directors of haemophilia centres in the United Kingdom. Issue 6680 (22nd April 1989) - Darby, S. C.; Rizza, C. R.; Doll, R.; Spooner, R. J.; Stratton, I. M.; Thakrar, B.
Abstract : OBJECTIVE--To estimate the cumulative incidence of AIDS by time since seroconversion in haemophiliacs positive for HIV and to examine the evidence for excess mortality associated with HIV in those who had not yet been diagnosed as having AIDS. DESIGN--Analysis of data from ongoing national surveys. SETTING--Haemophilia centres in the United Kingdom. PATIENTS--A total of 1201 men with haemophilia who had lived in the United Kingdom during 1980-7 and were positive for HIV. INTERVENTION--None. END POINTS--Diagnosis of AIDS; death in those not diagnosed as having AIDS. MEASUREMENTS AND MAIN RESULTS--Estimation of cumulative incidence of AIDS and number of excess deaths in seropositive patients not diagnosed with AIDS. Median follow up after seroconversion was 5 years 2 months. Eight five patients developed AIDS. Cumulative incidence of AIDS five years after seroconversion was 4% among patients aged less than 25 at first test positive for HIV, 6% among those aged 25-44, and 19% among those aged greater than or equal to 45. There was little evidence that type or severity of haemophilia or type of factor VIII or IX that had caused HIV infection affected the rate of progression to AIDS. Mortality was increased among those who had not been diagnosed as having AIDS, especially among those with "AIDS related complex." Thirteen deaths were observed among 36 patients diagnosed as having AIDS related complex against 0.65 expected, and 34 deaths in 1080 other patients against 22.77 expected; both calculations were based on mortality rates observed in haemophiliacs in the United Kingdom in the late 1970s. CONCLUSIONS--Rate of progression to AIDS depended strongly on age. There is a substantial burden of fatal disease among patients positive for HIV who have not been formally diagnosed as having AIDS.